Implementation of School-Based Management in Building Educational Quality at Nurul Hidayah Islamic Boarding School, Tapin Regency - Lailan Alfisyah; Husnul Madihah; Aam Gunawan (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to explain the implementation of School-Based Management (SBM) in improving the quality of education at the Nurul Hidayah Islamic Boarding School in Tapin Regency. Using a descriptive qualitative approach through observation, interviews, and documentation, this study involved leaders, teachers, and students as subjects. The results indicate that SBM is implemented through the Inspirational Class program (Literacy, Tahfidz, and Digital), which was collaboratively designed and implemented in a structured manner. This implementation has resulted in improved student competency, academic and non-academic achievement, and the achievement of B (Good) accreditation. This success is supported by visionary leadership, effective resource management, and ongoing supervision. This study concludes that SBM has successfully improved the quality of education comprehensively and can serve as a model for other institutions.